Penerapan Good School Governance (GSG) Dan Pengaruhnya Terhadap Efektifitas Pengelolaan Bantuan Operasional (BOS) Sekolah Dasar Kota Blitar - Hendri Susanti (Universitas Islam Kadiri, 2020)
This study aims to determine the effect of the application of good school governance on the effectiveness of the management of elementary school operational assistance. The method used is descriptive analysis method with a quantitative approach. The sample used saturated samples by showing all treasurers of primary school operational assistance as many as 48 people, data collected by questionnaire techniques while data analysis used multiple linear regression techniques. The results showed that participation had a positive and significant effect on the effectiveness of the management of school operational assistance, transparency had a positive and significant effect on the effectiveness of the management of school operational assistance, while accountability separately did not have a positive and significant effect on the effectiveness of the management of school operational assistance but together participation, transparency and accountability have a positive and significant effect on the effectiveness of managing school operational assistance.